2022
DOI: 10.1111/bcp.15587
|View full text |Cite
|
Sign up to set email alerts
|

Linezolid and the risk of QT interval prolongation: A pharmacovigilance study of the Food and Drug Administration Adverse Event Reporting System

Abstract: Aims: Few studies have investigated linezolid (LZD)-associated cardiotoxicity. This study explored the potential association between LZD and QT interval prolongation.Methods: Adverse event reports of QT interval prolongation associated with LZD from the Food and Drug Administration Adverse Event Reporting System from January 2013 to December 2021 were analysed and the reporting odds ratio (ROR) with 95% confidence intervals were calculated.Results: A total of 6738 adverse event reports of LZD as the primary an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
0
5
1
Order By: Relevance
“…Our data also reported adverse reactions consistent with those specified on the drug label, such as tongue discoloration (n = 70,) and tooth discoloration (n = 42,). A high incidence of vomiting and diarrhea has been reported in several previous studies (Li and Xu, 2018;Shi et al, 2023), but no positive signals were found after our disproportionality analysis. This may be because these adverse reactions are common with the adverse reaction reports for other drugs in the FAERS database, which in turn influences the signal value.…”
Section: Ades Related To Gastrointestinal Disorderscontrasting
confidence: 55%
See 3 more Smart Citations
“…Our data also reported adverse reactions consistent with those specified on the drug label, such as tongue discoloration (n = 70,) and tooth discoloration (n = 42,). A high incidence of vomiting and diarrhea has been reported in several previous studies (Li and Xu, 2018;Shi et al, 2023), but no positive signals were found after our disproportionality analysis. This may be because these adverse reactions are common with the adverse reaction reports for other drugs in the FAERS database, which in turn influences the signal value.…”
Section: Ades Related To Gastrointestinal Disorderscontrasting
confidence: 55%
“…Gastrointestinal-related symptoms (nausea, vomiting, and diarrhea) were the most common reasons for discontinuation of the drug (Moise et al, 2002;Noel et al, 2012). Nausea (Shorr et al, 2015), gastrointestinal intolerance (Veerman et al, 2023), diarrhea, and vomiting (Shi et al, 2023) were the most common side effects reported in previous studies. A single-center retrospective observational study (Tsutsumi et al, 2022) found that female gender is an independent risk factor for linezolid-induced vomiting, which may be associated with multiple signaling pathways including D2, 5-HT3, and neurokinin-1 receptors (Navari and Aapro, 2016).…”
Section: Gender-based Differencesmentioning
confidence: 86%
See 2 more Smart Citations
“…In the SHIELD trial, a precipitating cause could be identified in only 13% of electrical storms, typically represented by worsening heart failure, which should be treated in favor of better hemodynamic stability, and electrolyte disturbances [ 3 ]. Electrolyte abnormalities should be corrected, especially potassium [ 39 , 40 , 41 ] and magnesium serum levels: their deficiency may be associated with Torsade de Pointes (TdP), and intravenous magnesium might be effective even if magnesium serum levels are within range [ 42 ]. QT prolongation is often associated with recurrence of TdP, and in this setting, bradycardia may become a trigger factor: in fact, increasing cardiac frequency through beta adrenergic receptor stimulation (with isoproterenol) or transvenous pacing has proved to be effective.…”
Section: Early Evaluation and Acute Managementmentioning
confidence: 99%